Endocarditis - Tucker Oliver BS; Jose Vazquez MD, FACP, FIDSA (SAGE Publishing, 2023)
Severe infections due to Serratia marcescens have been documented with increasing frequency in persons who inject drugs and are frequently associated with nosocomial outbreaks. S marcescens endocarditis is rare, and there are very few, if any, reported cases secondary to an infected wound acquired at home. We present such a case in an immunocompetent 50-year-old man with paraplegia for 30 years and chronic decubitus ulcers who likely contracted the rare opportunistic Serratia following sacral wound contact with unclean surfaces in his hotel room bathroom. While it is also possible that the organism was obtained during a hospital admission 2 months before the positive blood cultures, he was found sitting with his ulcer in direct contact with red-pigmented accumulations on the shower floor. Therefore, it is more likely that he acquired the infection outside of the hospital setting. Early and effective management with advanced cardiac techniques and appropriate antibiotic coverage resulted in a positive outcome.